A detailed modular governor-turbine model for multiple-spool gas turbine with scrutiny of bleeding effect - Balaghi Enalou, Hossein; Abbasi Soreshjani, Eshagh; Rashed, Mohamed; Yeoh, Seang Shen; Bozhko, Serhiy (American Society of Mechanical Engineers, 2017)
Multiple-spool gas turbines are usually utilized for power supply in aircrafts, ships, and terrestrial electric utility plants. As a result, having a reliable model of them can aid with the control design process and stability analysis. Since several interconnected components are coupled both thermodynamically and through shafts, these engines cannot be modeled linearly as single shaft gas turbines. In this paper, intercomponent volume method (ICV) has been implemented for turbine modeling. A switched feedback control system incorporating bump-less transfer and antiwindup functionality is employed as governor for the engine. Validation with test results from a three spool gas turbine highlights high accuracy of turbine-governor model in various maneuvers. Results show that over-speed after load rejection is considerable due to the fact that in this arrangement, the power turbine (PT) is not coupled with the compressor which acts like a damper for single shaft gas turbines. To address this problem, bleed valves (mainly before combustion chamber) are used to arrest the over-speed by 20%. In addition, a switch is employed into the governor system to rapidly shift fuel to permissible minimum flow.